Meta-analysis of factors influencing depression in cervical cancer patients - Wang, Rong; Liu, Bang; Wei, Si-Wen; Liu, Yi-Ran; Zhong, Yi; Han, Li; Luo, Huai-Qing (Frontiers in Public Health, 2025)
BackgroundDepression in cervical cancer (CC) patients concurrently compromises disease management and quality of life. However, significant discrepancies persist among existing studies regarding the determinants of depression in this population worldwide. To address this gap, this study employs meta-analysis to systematically identify and synthesize the contributing factors to depression among cervical cancer patients.AimTo provide evidence-based references for mitigating depression risk among cervical cancer patients.MethodsLiterature was searched in databases including CNKI, Wanfang, VIP, CBM, Web of Science, PubMed, and EMBASE from their inception until March 2025. The literature was screened, selected, quality assessed, and data extracted and analyzed. Meta-analysis was conducted using Revman 5.4 and Stata 18 software, with odds ratios (OR) and their 95% confidence intervals (CI) as the observed indicators.ResultsA total of 1,108 articles were retrieved, with 15 articles ultimately included in the analysis. The results indicate that low educational attainment (OR = 3.25, 95% CI: 2.02–5.22), age ≥45 years (OR = 1.67, 95% CI: 1.09–2.55), inter-household monthly income disparity (OR = 3.06, 95% CI: 1.87–5.00), advanced tumor stage (OR = 1.99, 95% CI: 1.28–3.11), low social support (OR = 2.48, 95% CI: 1.95–3.16), moderate to severe pain (OR = 2.86, 95% CI: 1.76–4.65), limited disease awareness (OR = 2.58, 95% CI: 1.88–3.55), and undergoing hysterectomy (OR = 4.69, 95% CI: 3.03–7.24) are significant risk factors for depression in cervical cancer patients.ConclusionThe occurrence of depression in cervical cancer patients is influenced by multiple factors. Healthcare professionals and family members should conduct comprehensive assessments of patients' conditions to implement targeted prevention and intervention measures, thereby enhancing the psychological wellbeing of patients.Systematic review registrationhttps://inplasy.com/, identifier: INPLASY202560039.